Investigation and Systematic Risk Assessment in a Typical Contaminated Site of Hazardous Waste Treatment and Disposal - Wenhui Zhu; Xintong Yang; Jun He; Xiahui Wang; Ran Lu; Zheng Zhang (Frontiers Media S.A., 2021)
A total of 214 sampling sites of a hazardous waste disposal center were surveyed in a two-stage pollution investigation, including soil boreholes and groundwater monitoring wells. Results showed that chemical oxygen demand (COD) (4.00-2930.00 mg/L), fluoride (0.07-9.08 mg/L), chromium (0.12-1.20 μg/L), nickel (0.15-459.00 μg/L), lead (0.10-10.20 μg/L), cadmium (Cd) (0.05-16.40 μg/L), and beryllium (0.06-3.48 μg/L) were detected in groundwater samples. For soils, Cd in soil (78.7 mg/kg) exceeded the risk screening value (65 mg/kg) for soil contamination of the second type of development land (GB36600-2018), and there remained the risk of leakage in the landfill detection investigation. Then, a health risk assessment was carried out. Based on the definitions of the groundwater exposure pathway (HJ 25.3-2019) and the pollution investigation of groundwater, the carcinogenic and non-carcinogenic risks of groundwater were generally considered to be negligible. The carcinogenic risk and non-carcinogenic risk of the concerned pollutant in soil for risk assessment (Cd) under the condition of reutilization exceeded the corresponding acceptable levels (1E-06 and 1). The (non-)carcinogenic risk of Cd mainly came from oral intake of soil and inhalation of soil particles under two conditions of reutilization and non-utilization, so on-site workers and surrounding residents should be properly protected from the mouth and nose to minimize the intake of pollutants from the soil and soil particles. The area of soil contaminated by Cd was about 630.58 m2, and the amount of pollution was about 1261.16 m3. The heavy metal pollution was only distributed in the depth range of 0-2 m, and the suggested risk control value of soil pollutants under the condition of reutilization for Cd was 56 mg/kg. Based on different pollution characteristics of soil, groundwater, and the landfill, targeted control measures were proposed.